MANAJEMAN PENCEGAHAN DAN PENGENDALIAN COVID-19 DI UNIT KERJA REKAM MEDIS - Rika Andriani (Program Studi Perekam Medis & Informasi Kesehatan, 2021)
Background: Medical records staffs face the occupational risk of becoming infected with COVID-19. To minimize the risk of exposure to the SARS-COV-2 virus, COVID-19 control and prevention are need to implemented in medical records unit.Methods: This article is a literature study. This literature study is limited to COVID-19 control and prevention in the medical records unit. This study used journal articles, reports, manuals, and regulations from PubMed, IEEE, Springer, NCBI, BMJ Journals, ScienceDirect, and Google Scholar.Result: PORMIKI published a circular letter about work procedures for medical record staffs in the COVID-19 pandemic situation, but it has not specifically mentioned the management of prevention and control in medical records unit yet.Conclusion: COVID-19 controls and preventions in medical records unit can be implemented with engineering controls such as redesign medical records unit office and disinfection the office equipments in medical records unit office; administrative controls such as create procedures in the admission unit, create procedures to fill and return medical records files, and use electronic medical records; and use personal protective equipment according to job risks.Keywords: medical records unit management, COVID-19 control and prevention